The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0156127
|View full text |Cite
|
Sign up to set email alerts
|

Strict Selection Alone of Patients Undergoing Liver Transplantation for Hilar Cholangiocarcinoma Is Associated with Improved Survival

Abstract: Liver transplantation for hilar cholangiocarcinoma (hCCA) has regained attention since the Mayo Clinic reported their favorable results with the use of a neo-adjuvant chemoradiation protocol. However, debate remains whether the success of the protocol should be attributed to the neo-adjuvant therapy or to the strict selection criteria that are being applied. The aim of this study was to investigate the value of patient selection alone on the outcome of liver transplantation for hCCA. In this retrospective stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 22 publications
1
55
0
6
Order By: Relevance
“…A sample of these studies is cited in the references of the manuscript. With reports concerning LT for specific hepatic diseases [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], analysis of the impact of the type of preservation solution [25], and of the immunosuppressive regimen on the patient outcome [26], ELTR has helped develop risk models for mortality following liver-transplantation [27,28]. Owing to the large cohort of patients, the exhaustiveness, and quality of the data, and the long follow-up provided by the ELTR, the results are really representative of LT in Europe.…”
Section: Previous Eltr Achievementsmentioning
confidence: 99%
“…A sample of these studies is cited in the references of the manuscript. With reports concerning LT for specific hepatic diseases [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], analysis of the impact of the type of preservation solution [25], and of the immunosuppressive regimen on the patient outcome [26], ELTR has helped develop risk models for mortality following liver-transplantation [27,28]. Owing to the large cohort of patients, the exhaustiveness, and quality of the data, and the long follow-up provided by the ELTR, the results are really representative of LT in Europe.…”
Section: Previous Eltr Achievementsmentioning
confidence: 99%
“…Studies showed improved 5‑year survival rates of over 70% when OLT was combined with neoadjuvant chemoradiotherapy in selected patients (the “Mayo protocol”) [ 66 , 109 , 110 ]. However, a multicentre analysis of the European Liver Transplant Registry in 2016 revealed comparably promising results without chemoradiation when the same strict selection criteria (hECC <3 cm, negative lymph nodes, no metastasis) were applied as in the Mayo study, therefore questioning the true contribution of pre-transplant therapy to overall survival [ 111 ]. A very recent multicentre study from the USA further challenged resection as the gold standard for hECC within these criteria, by showing that OLT (with preoperative treatment) results in substantially improved 5‑year OS of 54% versus 29% after resection [ 112 ].…”
Section: Cholangiocarcinomamentioning
confidence: 99%
“…In this retrospective study, patients who complied with the Mayo Clinic criteria (group A) showed a significantly better survival compared to patients who did not meet the criteria (group B). The 5-year survival rate was 59% for group A versus 21% for group B (P = 0.001) (9). The ongoing French phase III TRANSPHIL trial should help determine whether this treatment should be the standard treatment for cholangiocarcinoma.…”
Section: Esmo Clinical Practice Guidelinesmentioning
confidence: 99%